دراسة الفعالية البيولوجية لنبات اللبين Euphorbia-Guyoniana (Boiss. & Reut) - بوراس, رانيا (جامعة الوادي University of Eloued, 2016)
ظَرا نلإهخ اًو انكبير ي طرف انبااثيي اان بُاحااث انيبيات تخداخهاايبا ئبااا م ػا االتصات ان اًا ؼُت اث انخايريراث انجا بَيات ػها صا ت اس نَاا ار اَاا ن نًااه تً ابالا انب ام ان خً يًام اث ل ادات حايرير ينخههاااث بَخاات - guyoniana ان خً ااام ػهيبااا سدااخه اسصيا وَل انبكنا اإحباع طرصقت ان قُغ ػه انبا ل اإخخ ف انزي ي ] 84 دا 27 دا[.ػه أ اؼت ا وَاع ي انبكخيرصااا . تاااا خػخ اًاا اَ ػهاا أااابر انياارو ان يًكرتايونومياات ان ؼً اًاول ابااا ااث ان نًخ اا ياث, تهااث طرصقاات اس خَ ا ػه اااراBecause of the considerable interest by researchers of medical plants and the use of these latter as substitutes for manufactured medicines with their side effects impact on human health; we decided to contribute to the effect of the Euphorbia guyoniana extracts obtained via the process extractions using two different solvants (ethanol and hexane) depending on time (48 – 72 h) opting for the maceration method on four types of bacteria. , which is the disk difusion method. The study showed that the biological evaluation obtained from the Plant Extracts against types of gram- and gram+ bacteria gave different results depending on the different kind of bacteria except the ethanol extract 48 hours did not show any effectiveness on the tested bacteria. Comparing the inhibition effect, the ethanol extract for 72 hours was the most effective among them. Therefore, we can say
مذكرة ماستر تخصص كيمياء
Keywords: : - ,ان يًكرتايونوميت, انبكخيرصا, طرصقت اس خَ ا; Euphorbia-guyoniana, microbiological, bacteria, extraction